Occurrence, migration, and ecological risk assessment of Neonicotinoid insecticides in water and sediments of Dongting Lake, China - Xiong Mao; Yi Huang; Zhi-tao Huo; Jun Guo; Cong Li; Feng-cun Huang (China Geology, 2025)
ABSTRACT: Neonicotinoid insecticides (NEOs) have become an integral part of the global insecticide market due to their high efficiency and low toxicity. However, their environmental persistence has raised significant ecological concerns. Dongting Lake represents a vital freshwater lake in China, and its ecosystem health directly affects regional ecological balance and people’s livelihoods. This study systematically investigated the occurrence characteristics and ecological risks of NEOs in water bodies and sediments across the Dongting Lake basin. Based on surface water and sediment samples collected from 26 representative sampling sites, this study quantified nine NEOs using liquid chromatography triple quadrupole mass spectrometry. Furthermore, it assessed ecological risks posed by the NEOs using the risk quotient (RQ) method and fugacity modeling. The results revealed the presence of six NEOs in the water bodies: imidacloprid (IMI), acetamiprid (ACE), clothianidin (CLO), thiamethoxam (THIA), flonicamid (FLO), and dinotefuran (DIN). The total concentrations of these six NEOs averaged 275.11 ng/L. Five predominant NEOs (i.e., IMI, THIA, ACE, CLO, and DIN) were identified in the sediments, with a mean concentration of 0.31 ng/g. The NEO concentrations in the water bodies across the Dongting Lake basin increased in the order of the Xiangjiang, Zishui, Yuanjiang, and Lishui rivers (collectively referred to as the Four Rivers), the mainstream of Dongting Lake, the Xinqiang River, the Miluo River, and the Hudu, Ouchi, and Songzi rivers (collectively referred to as the Three Outlets). Sediments from tributaries progressively accumulate in the lake. The ecological risk assessment identified IMI and DIN as the highest-risk compounds (RQ > 1), with high-risk areas concentrated in the mainstream of Dongting Lake and the Ouchi, Miluo, and Hudu rivers. The fugacity model showed that IMI, ACE, and THIA are prone to diffuse from sediments to water bodies in most areas, with fugacity fractions (ff) values of greater than 0.5. In contrast, the mainstream of Dongting Lake acts as a sink of CLO and DIN (ff values: < 0.5). Sediments at the lake’s outlet emerge as an important sink of NEOs. Based on the results of this study, it is advisable to strengthen the supervision of NEO applications in agricultural areas and to implement zonal control strategies. These measures will help reduce ecological risks and protect the safety of water ecosystems in the Dongting Lake region.